Penerapan Metode PBL Dalam Pencatatan Sediaan Pada Proses Produksi TFME Polibatam - Seto Sulaksono Adi Wibowo; Sugeng Riadi; Riri Zelmiyanti; Yosi Handayani (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2022)
An orderly and accurate inventory recording system will provide convenience in managing all types of inventory owned. The reliability of information on the amount of inventory will facilitate operations/production activities that will be and are being worked on. The availability of reliable and valid information is a weak point in the production unit at TFME. The lack of competence of human resources involved in operating activities is one of the main reasons why there is no inventory information available. This study aims to improve the inventory recording system that applies. Starting from stock taking, naming supplies to providing a good and easy-to-read recording format for users. The results of this study can be used as one of the improvement agendas in operating process governance. Case studies by directly identifying the location are an option in carrying out this research. All data were collected through interviews and direct calculations of the types of stocks owned. The correct recording process according to the period of incoming and outgoing supplies will be applied in the form of a stock card in a format that is easy for users to understand.